SUCCESSION OF LACTIC ACID BACTERIA ON CANDIED PAKOBA FRUIT (Syzygium luzonense) - Kembuan, Patricia Pericilia; Mokosuli, Yeremia Samuel; Lawalata, Helen J.; Moko, Emma; Roring, Verawati I. Y (LPPM Politeknik Saint Paul Sorong, 2024)
Pakoba fruit is often made into sweets, salad, pickles because it has a very sour taste and is a habitat for lactic acid bacteria. The purpose of this study was to determine the characteristics of lactic acid bacteria succession during the fermentation process of candied pakoba fruit. This research is an explorative research. The number of microbes was observed starting from day 0, 1, 3 and 7. Based on the results of identification data, 12 bacterial isolates were obtained in pakoba fruit fermentation. The isolates obtained were then macroscopically identified and microscopically identified. 12 isolates were round, 12 isolates had enpitire edges, 12 isolates had raised elevations, 12 isolates had covex colony surfaces, 10 isolates were white and 2 isolates were cream-colored. Of the 12 isolates, it was found that the bacteria that grew in the fermentation of candied pakoba fruit after profile matching was suspected of the genus Lactobacilus sp. and Leucunostoc.